Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1523/jneurosci.16-23-07566.1996
|View full text |Cite
|
Sign up to set email alerts
|

Differential Actions of Serotonin, Mediated by 5-HT1Band 5-HT2CReceptors, on GABA-Mediated Synaptic Input to Rat Substantia Nigra Pars Reticulata NeuronsIn Vitro

Abstract: The ability of serotonin to modulate GABA-mediated synaptic input to substantia nigra pars reticulata (SNr) neurons was investigated with the use of whole-cell patch-clamp recording from slices of rat midbrain. Fast evoked GABA(A) receptor-mediated synaptic currents (IPSCs) were attenuated reversibly approximately 60% by serotonin, which also caused an inward current with reversal potential of -25 mV. This inward current was blocked by the 5-HT2 receptor antagonist ritanserin, whereas the IPSC depression was b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
93
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 56 publications
16
93
0
Order By: Relevance
“…This action is likely indirect since stimulation of 5-HT 2C receptors induces membrane depolarization and neuronal excitation (Di Giovanni et al, 2001;Sheldon and Aghajanian, 1991;Stanford and Lacey, 1996). Examination of the patterns of expression of 5-HT 2C receptor mRNA indicates that 5-HT 2C receptors are localized to GABA-ergic, and not dopaminergic neurons, in the VTA (Eberle Wang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This action is likely indirect since stimulation of 5-HT 2C receptors induces membrane depolarization and neuronal excitation (Di Giovanni et al, 2001;Sheldon and Aghajanian, 1991;Stanford and Lacey, 1996). Examination of the patterns of expression of 5-HT 2C receptor mRNA indicates that 5-HT 2C receptors are localized to GABA-ergic, and not dopaminergic neurons, in the VTA (Eberle Wang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For example, systemic and microiontophoretic administration of the 5-HT 2C/1B agonist meta-chlorophenylpiperazine (mCPP) decreased the firing rate of VTA DA neurons; the systemic actions of mCPP were antagonized by the 5-HT 2/1A antagonist mesulergine, which alone increased firing rates of a subpopulation of these cells (Prisco et al 1994;Prisco and Esposito 1995). Although 5-HT 2C/2B/1B ligands failed to alter the firing characteristics of DA neurons in the substantia nigra (Kelland et al 1990; but see Stanford and Lacey 1996), the activity of VTA DA neurons is reported to increase following administration of the 5-HT 2C/2B antagonists SB 200646A (Ashby and Minabe 1996) or SB 206553 (Lejeune et al 1997). These results suggest that 5-HT 2C/2B receptors may tonically inhibit cell firing of DA neurons in the VTA.…”
mentioning
confidence: 99%
“…The agonists that mimicked that effect were only of the 5-HT 1B class (CP 93129 and TFMPP). Neither the 5-HT 2 antagonist ritanserin nor the GABA A antagonist bicuculline were able to block that inhibition, suggesting that, in addition to an indirect action (Stanford and Lacey, 1996), some SNr neurons may be directly inhibited by 5-HT.…”
Section: -Ht Modulation Of Snr Activitymentioning
confidence: 95%
“…The inhibition of SNr neurons by 5-HT is supported by the finding that unilateral injection of 5-HT, 5-HT 1D agonist and selective serotonin reuptake inhibitors (SSRIs) into the SNr of freely moving rats elicited a contraversive circling behaviour (James and Starr, 1980;Blackburn et al, 1981;Oberlander et al, 1981;Higgins et al, 1991;Bata-Garcia et al, 2002) as muscimol does (Oberlander et al, 1981). In spite of this evidence, Lacey and co-workers have shown, by using in vitro electrophysiological methods, that 5-HT not only directly excites SNr neurons but also disinhibits them by reducing GABA release from striatonigral terminals, acting on presynaptic 5-HT 1B receptors (Rick et al, 1995;Stanford and Lacey, 1996). On the other hand, a subsequent electrophysiological in vitro study demonstrated also a direct inhibitory action of 5-HT on SNr neurons (Gongora-Alfaro et al, 1997).…”
Section: -Ht Modulation Of Snr Activitymentioning
confidence: 99%